Dynamics of long polyunsaturated fatty acids in rat brain - Barceló-Coblijn, Gwendolyn (Acta Biologica Szegediensis, 2003)
Unhealthy dietary habit e.g. lipid rich diet could result in inflammatory processes and necrosis in the gastrointestinal tract in which free radical reactions are involved. Higher plants have many free radical scavenger molecules and anti-inflammatory compounds in wonderful variations. Sempervivum tectorum L. is well known plant in folk medicine. In the case of complex plant extracts, such as Sempervivum tectorum ones, which contain several active compounds, it is impossible to discover the single mechanism of action, therefore practically the reducing activity have to be measured in vitro and in rat intestinal tract in vivo.The question was, whether the absorbed active compounds of Sempervivum tectorum extract were able to influence on the changed cellular redox states in mucosa of all part of intestinal tract in experimental bowel disease. This biochemical work presents the protective effect of natural polyphenols and flavonoids of Sempervivum tectorum extract in bowel disease - especially in jejunum and ileum - induced by high dietary triglyceride and cholesterol level in rats.